Observed Teaching Styles of Junior Development and Club Professional Tennis Coaches in Australia - Hewitt , Mitchell; Edwards, Kenneth (ITF Coaching & Sport Science Review, 2013)
Diverse learning conditions and experiences are often created by employing different teaching styles and tennis coaches need to purposefully implement a range of teaching styles. This paper presents the findings of research completed on the observed teaching styles of 12 tennis coaches in Australia using Mosston and Ashworth’s Spectrum of Teaching Styles (2008). The 12 coaches were selected after completing a survey questionnaire about teaching styles and indicating their willingness to participate in systematic observations of their instructional practices. Results indicate that Junior Development and Club Professional tennis coaches commonly use two teaching styles (Command Style-A and Practice Style-B. These teaching styles share common and complimentary pedagogical principles with direct instruction guidelines whereby the coach is in control of what the students are learning in addition to how and why they are learning it.